Polymer grafted smart mesoporous silica nanoparticles: challenges and advances in controlled drug delivery applications - Badiger, M. V.; Tiwari, N. (Nova Science Publishers, Inc., 2018)
The application of nanoparticles to intracellular drug delivery has attracted increasing attention in the last few decades. Among them, mesoporous silica nanoparticles (MSNs) have emerged as promising nanomaterials which have shown great potential towards incubation of both hydrophobic and hydrophilic drugs and their further internalization at the targeted site in physiological environment for the treatment of large number of diseases. Excellent properties of MSNs such as good stability control over morphology and tunable particle size and the pore structure gives them an edge over other organic or inorganic based nanoparticles. With these properties, there is a great scope in designing novel MSNs with functionalization at the surface as well as within the pores using biocompatible and biodegradable polymers, stimuli responsive groups, proteins etc. MSNs have shown great potential in biotechnological and biomedical applications. Efforts are also made to increase the biocompatibility and circulation time of drug loaded MSNs by coating various polymers onto the surface of MSNs. Extensive work on MSNs has been reported in the literature which is however scattered. In the present chapter, we have dealt with the advances made in MSNs as controlled and targeted drug delivery systems using either synthetic or natural polymers specifically towards cancer treatment.